A method for preparing spherical titanium carbide nanoparticles based on direct reaction of metal titanium powder and carbon black

CN123002847APending Publication Date: 2026-10-30CISDI ENGINEERING CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611404062.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0010]有鉴于此,本发明的目的在于提供一种基于金属钛粉与碳黑直接反应制备球形碳化钛纳米颗粒的方法,以解决现有技术中金属钛粉与碳黑直接反应制备碳化钛时产物粒径不可控(易长大)和形貌不规则的技术难题

Benefits of technology

(一)有效解决了直接反应路线的两大固有难题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002847A_ABST
    Figure CN123002847A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing spherical titanium carbide nanoparticles based on direct reaction of metal titanium powder and carbon black, and belongs to the technical field of nanometer material preparation. In view of the problem that strong heat release and high-temperature sintering in Ti+C direct reaction cause particles to easily grow to a submicron level and have irregular morphology, spherical metal titanium powder is selected as a morphology template, low-structure ultrafine carbon black is selected as a carbon source, and a precursor powder is obtained through high-energy ball milling of the metal titanium powder and the carbon black and NaCl-KCl molten salt; carbonization reaction is carried out through multi-stage heating in an inert atmosphere, the molten salt liquid-state "micro-reaction pool" is used to physically isolate particles, and excessive carbon black is used to chemically pin particles to inhibit surface diffusion of the particles; after the reaction, the particle size is frozen through segmented speed control cooling, and then the product is obtained through water washing and vacuum drying. The obtained particles have an average particle size of 40-60 nm, a sphericity of greater than 0.90, and an oxygen content of less than 0.5wt%. The method is simple, has good repeatability, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterial preparation technology, specifically relating to a method for preparing spherical titanium carbide nanoparticles through direct carbonization reaction using metallic titanium powder and carbon black as raw materials. In particular, it relates to a method for controllably preparing titanium carbide nanoparticles with an average particle size of 40-60 nm and a sphericity greater than 0.90 by synergistic control of multiple strategies, including high-energy ball milling activation, physical isolation in molten salt medium, chemical pinning of excess carbon, and precise thermal field management. Background Technology

[0002] Titanium carbide (TiC) possesses ultra-high hardness (HV ~28-35 GPa), a high melting point (~3160℃), excellent electrical and thermal conductivity, and chemical stability, making it widely used in cutting tools, wear-resistant coatings, metal matrix composite reinforcements, and electrocatalysis. Studies have shown that when the TiC particle size is reduced to around 50 nm and exhibits good sphericity, its reinforcing effect as a composite material reinforcing phase can be significantly improved, while its electrocatalytic activity and chemical stability also show a clear size-dependent effect.

[0003] Currently, the main methods for preparing titanium carbide nanoparticles include the following: Carbothermic reduction method: TiC is prepared by carbothermic reduction reaction of TiO2 and carbon black at high temperature (TiO2 + 3C → TiC + 2CO↑). This method has low raw material cost, but the reaction temperature usually needs to be above 1300℃. The high temperature causes severe sintering and growth of particles, making it difficult to obtain nanoscale products, and the product morphology is mostly irregular blocky or polyhedral. For example, Chinese patent CN101734659A discloses a method for preparing titanium carbide powder by high-frequency induction-carbothermic reduction, using titanium dioxide and carbon as raw materials, and carrying out carbothermic reduction reaction by high-frequency induction heating to 1600-1800℃ and holding at that temperature. The product obtained is only submicron-sized titanium carbide powder with a particle size of less than 1μm.

[0004] Sol-gel method: Using titanate esters and carbon sources as raw materials, a precursor is prepared through a sol-gel process, followed by high-temperature carbonization to obtain TiC. For example, Chinese patent CN102674350A discloses a method for preparing titanium carbide nanoparticles. A carbon sol is prepared using resorcinol and formaldehyde as raw materials, and a titanium sol is prepared using tetrabutyl titanate or tetraethyl titanate as raw materials. The two are mixed and subjected to a sol-gel reaction, aging, and drying to obtain the precursor. Then, multiple processes including carbothermic reduction, calcination, acid leaching, water washing, and drying are performed to obtain titanium carbide nanoparticles. Although this method can prepare nanoscale particles, the process is complex, time-consuming, has low yield, and the cost of organic raw materials is high, making it unsuitable for large-scale production.

[0005] Plasma method: This method utilizes DC arc plasma or radio frequency plasma as a heat source to prepare nanoscale titanium carbide powder. For example, Chinese patent CN1445163A discloses a process for preparing titanium carbide ceramic powder using plasma chemical vapor synthesis. This process uses DC arc plasma as a heat source to rapidly decompose and synthesize titanium tetrachloride with liquefied gas in a plasma reactor, followed by quenching to obtain nanoscale titanium carbide powder. This method produces products with high purity and small particle size, but the equipment is expensive, energy consumption is high, and production costs are high, limiting its large-scale industrial application.

[0006] Molten salt method: Titanium carbide is prepared by reacting a titanium source with a carbon source in a molten salt medium. For example, Chinese patent CN117051507A discloses a method for preparing titanium carbide fibers, using titanium hydride as the titanium source, carbon nanotubes as the carbon source, and NaCl-KCl as the molten salt medium, reacting at 700–900℃ under argon protection to obtain fibrous titanium carbide; Chinese patent CN1299982C discloses a method for preparing titanium carbide materials by molten salt reaction, reacting metallic titanium with carbon materials in a molten salt medium such as alkali metal or alkaline earth metal chlorides at 600–1300℃ to prepare titanium carbide powder. However, these methods either produce fibrous rather than spherical particles, or do not provide specific process solutions for precise particle size control within 50nm.

[0007] The direct high-temperature reaction of titanium powder and carbon black (Ti + C → TiC) is the simplest synthesis route, offering significant advantages such as readily available and inexpensive raw materials, a short process flow, and high atom economy. Chinese patent application CN104230343A discloses a method for synthesizing titanium carbide micropowder using high-frequency induction thermal explosion. This method uses Ti powder and carbon black as base materials and Al powder or Zn powder as additives. The low-melting-point additives are used to dilute the combustion temperature, thus inhibiting the growth and coarsening of TiC grains, resulting in a product particle size of 50-80 nm. However, the thermal explosion reaction is completed instantaneously, making it impossible to programmatically control the heating, holding, and cooling processes. The product is an irregularly shaped micropowder, and sphericity control is not addressed. Furthermore, this reaction faces two inherent challenges: First, the strongly exothermic reaction leads to particle growth. The enthalpy change ΔH for the reaction Ti + C → TiC is approximately equal to... At 184 kJ / mol, this is a strongly exothermic reaction. Once initiated, the local temperature rises sharply, leading to intense Ostwald ripening and sintering growth of the grains, with the product particle size rapidly increasing from the nanometer scale to the submicrometer or even the micrometer scale.

[0008] Secondly, the morphology is difficult to control. The solid-state reaction between titanium powder and carbon black usually takes place with titanium particles as a "template," and the product inherits the angular characteristics of the raw material, forming an irregular polyhedral morphology. Even when using nano-titanium powder, the anisotropic crystal growth at high temperatures can easily destroy the spherical morphology.

[0009] Therefore, how to effectively control the product particle size to around 50 nm and maintain good sphericity while keeping the direct reaction route of Ti + C simple is an urgent technical problem to be solved. Summary of the Invention

[0010] In view of this, the purpose of this invention is to provide a method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black, so as to solve the technical problems of uncontrollable particle size (easy growth) and irregular morphology of the product in the direct reaction of metallic titanium powder and carbon black to prepare titanium carbide in the prior art. This method adopts a three-in-one morphology and particle size synergistic control strategy of "spherical titanium powder template inheritance + physical isolation of molten salt micro-reaction pool + chemical pinning of excess carbon black", combined with a refined multi-stage heating and segmented rate-controlled cooling thermal field management system, to achieve the controllable preparation of titanium carbide nanoparticles with an average particle size of 40-60 nm and a sphericity greater than 0.90.

[0011] To achieve the above objectives, the present invention provides the following technical solution: The overall process flow of this invention is as follows: Figure 1 As shown, the process is divided into three stages: pretreatment, reaction and cooling, and post-treatment, which include five steps in sequence: S1 raw material preparation, S2 high-energy ball milling activation, S3 carbonization reaction (including sample loading and atmosphere replacement), S4 segmented rate-controlled cooling, and S5 post-treatment. The specific technical solutions for each process are as follows: S1. Raw material preparation NaCl and KCl are mixed in a molar ratio of 1:1 (eutectic melting point 657℃), dried under vacuum at 150-250℃ for 12-48 hours, and then ground in an inert atmosphere glove box to obtain NaCl-KCl molten salt (hereinafter referred to as molten salt).

[0012] In an inert atmosphere glove box, spherical titanium powder, carbon black, and the molten salt are weighed out. The average particle size of the spherical titanium powder is ≤50nm, preferably 30-40nm, with a sphericity >0.85 and a purity >99.5%. The spherical titanium powder serves as a "morphology template," and its spherical morphology can be inherited during the carbonization reaction, which is the first mechanism to ensure the sphericity of the final product.

[0013] The carbon black is a low-structure ultrafine carbon black with a primary particle size of 30-50 nm, a specific surface area ≥50 m² / g, and an oil absorption value (DBP) of 100-200 mL / 100 g. The low-structure carbon black has a compact, near-spherical aggregate structure, which, after ball milling, can uniformly coat titanium particles. It is also less prone to forming stubborn carbon skeleton residues after the reaction, serving as a second mechanism to ensure the sphericity of the product.

[0014] The molar ratio of titanium powder to carbon black is Ti:C = 1:1.1-1.3, preferably 1:1.15. An excess of 15% carbon can simultaneously provide physical isolation, surface chemical pinning, and in-situ deoxidation (see details below).

[0015] The mass ratio of the molten salt to the total mass of titanium powder and carbon black is 5:1-20:1, preferably 10:1. Sufficient molten salt can form a large number of isolated "micro-reaction pools", which is the core guarantee for achieving nano-particle size.

[0016] S2, High-energy ball milling activation The titanium powder, carbon black, and molten salt obtained in step S1 are placed in a ball mill jar and subjected to high-energy ball milling under an inert atmosphere. The ball milling speed is 400-600 rpm, the ball milling time is 12-20 hours, and the ball-to-powder ratio is 10:1-20:1. Wet milling is preferred, using anhydrous cyclohexane or anhydrous ethanol as the wet milling medium. After ball milling, the wet milling medium is removed by vacuum drying to obtain the precursor powder. The ball mill jar and the milling medium are made of titanium carbide cemented carbide or zirconium oxide to reduce metallic impurities introduced by abrasion.

[0017] The high-energy ball mill performs three functions in this invention: Nanoscale uniform mixing: Titanium powder, carbon black and molten salt are uniformly dispersed at the molecular level under mechanical force, shortening the diffusion distance between Ti and C; Lattice activation: Introducing a large number of lattice defects and amorphization into titanium powder reduces the starting temperature of the carbonization reaction from the conventional 1100-1200℃ to 900-1000℃. The reduction in reaction temperature directly weakens the thermodynamic driving force for grain growth. Constructing a "precursor / salt" composite micro-region: embedding nano-sized titanium particles and carbon black particles into the salt grains, laying the structural foundation for the subsequent formation of the molten salt "micro-reaction pool".

[0018] S3, carbonization reaction The precursor powder obtained in step S2 is spread evenly in a corundum container, with a powder thickness not exceeding 5 mm. The corundum container is placed in a tube furnace, and the furnace tube is evacuated and then purged with inert gas until the pressure inside the furnace tube is ≤10. - ²Pa, repeat at least three times. After the last inflation, maintain an inert gas flow at a flow rate of 50-200 mL / min. The inert gas is preferably argon.

[0019] Under an inert atmosphere, the furnace temperature is raised to 900-1000℃ according to a multi-stage heating program for carbonization reaction, and held for 120-240 minutes.

[0020] The design logic of the multi-stage heating program is as follows: Stage I (room temperature → 200℃): Heating rate 8-12℃ / min. Rapidly removes physically adsorbed water, preventing water vapor from reacting with titanium powder at high temperatures to form a TiO2 passivation layer.

[0021] Stage II (200℃→400℃): Heating rate 4-6℃ / min, holding at 400℃ for 30-90min. During this stage, an Ar + 5% H2 mixture is introduced. The H2 reacts with the adsorbed oxygen and thin oxide layer on the titanium powder surface to reduce the oxygen content, activating the titanium surface and promoting subsequent carbonization. In this temperature range, H2 does not react significantly with carbon, ensuring safety and controllability. After this stage, the atmosphere is switched back to pure Ar.

[0022] Stage III (400℃→700℃): Heating rate 1-3℃ / min, hold at 700℃ for 20-40 min. This stage is the molten salt melting and venting section. The molten salt begins to melt at 657℃. Slow heating ensures uniform melting of the salt and full coating of reactant particles, while allowing residual gas to escape smoothly, avoiding bubble formation that could lead to uneven micro-reaction.

[0023] Stage IV (700℃→1000℃): Heating rate 4-6℃ / min. Rapidly heat to the reaction temperature to shorten the residence time in the intermediate temperature zone and inhibit low-temperature Ostwald ripening.

[0024] Stage V (900-1000℃ isothermal): Hold for 120-240 min. Carburization reaction stage. Ti and C react in the molten salt "micro-reaction pool" to form TiC. Extend the holding time to ensure complete carburization, but the temperature should not exceed 1000℃ to inhibit grain growth.

[0025] During this stage, the molten salt medium exerts a triple effect: Physical barrier: Liquid salts coat the Ti-C reactant particles, forming countless independent "micro-reaction pools" that prevent the generated TiC particles from directly contacting and sintering. This is the most critical guarantee for locking the particle size at the nanoscale. Endothermic buffer: The melting and heating of the salt absorbs a large amount of heat, effectively suppressing local overheating caused by the exothermic reaction of Ti+C; Morphology control: In a liquid phase environment, newly generated TiC crystal nuclei tend to grow in the equiaxed crystal morphology with the lowest surface energy through surface diffusion, which is beneficial to maintaining the spherical morphology.

[0026] Meanwhile, excess carbon black (Ti:C=1:1.15) exerts a chemical pinning effect at this stage: carbon black particles are adsorbed on the surface of newly formed TiC crystal nuclei, forming a transient carbon enrichment layer, increasing the energy barrier for atomic migration on the TiC surface, and inhibiting surface diffusion-controlled Ostwald ripening.

[0027] S4, Segmented Speed ​​Controlled Cooling After the carbonization reaction is completed, the furnace temperature is reduced to room temperature according to a segmented, rate-controlled cooling procedure: 900-1000℃→800℃: Cooling rate 10-15℃ / min, preferably 12℃ / min, using programmed temperature control combined with auxiliary airflow cooling (introducing compressed air or flowing Ar gas into the outer wall of the furnace tube or the furnace jacket). Rapidly traverses the high-temperature zone, freezing grain size and inhibiting grain boundary migration and Ostwald ripening.

[0028] 800℃→500℃: Cooling rate 5-8℃ / min, preferably 6℃ / min, using programmed temperature control. During this range, the molten salt begins to solidify (NaCl-KCl eutectic solidification point is about 657℃). Moderate cooling allows the salt matrix to shrink uniformly, preventing TiC particles from breaking due to thermal stress.

[0029] 500℃ → Room temperature: Allow to cool naturally, turn off the heating power, and maintain Ar flow. Slow cooling in the low-temperature region eliminates residual stress, and when the temperature is low enough, there is no longer a risk of grain growth.

[0030] The key to the segmented, rate-controlled cooling design lies in the fact that the cooling rate in the high-temperature zone determines whether the particle size can be effectively "frozen," serving as the final barrier to inhibit Ostwald ripening; while the cooling rate in the medium-temperature zone affects the stress exerted on the particles during molten salt solidification. The synergy between these two factors is crucial for ensuring the particle size and integrity of the product.

[0031] S5, Post-processing The product obtained in step S4 was placed in deionized water at a solid-liquid ratio of 1:50-1:100, heated to 70-90℃ and stirred for 2-8 hours, during which fresh deionized water could be replaced, and ultrasonic treatment was also performed. Then, solid-liquid separation was performed by vacuum filtration with a filter membrane pore size of 0.22μm.

[0032] The filter cake was redispersed in fresh deionized water and washed repeatedly until the conductivity of the filtrate was <5 μS / cm (qualitative analysis with AgNO3 solution showed no white precipitate), ensuring that Cl... - Completely remove.

[0033] The washed filter cake is vacuum dried at 60-80℃ and a vacuum degree <-0.1MPa for 12-24 hours. Vacuum drying allows water to evaporate at a lower temperature under negative pressure, avoiding hard agglomeration caused by surface tension at the liquid-gas interface in conventional oven drying.

[0034] After drying, the particles are gently ground in an inert atmosphere glove box with an agate mortar for 5-10 minutes to eliminate slight agglomeration and obtain well-dispersed spherical titanium carbide nanoparticles.

[0035] The spherical titanium carbide nanoparticles prepared by the above method, under the preferred process conditions (Ti:C=1:1.15, molten salt ratio 10:1), have an average particle size of 40-60 nm, a sphericity greater than 0.90, an oxygen content of less than 0.5 wt%, a residual carbon content of less than 3 wt%, and XRD shows that they are pure-phase cubic TiC.

[0036] The beneficial effects of this invention are as follows: (i) It effectively solved the two inherent problems of the direct reaction route. This invention addresses two major technical bottlenecks in the direct reaction of titanium powder and carbon black (Ti+C→TiC): particle growth and irregular morphology. Through a synergistic three-pronged control strategy—"spherical titanium powder template inheritance + physical isolation in a molten salt microreactor + chemical pinning with excess carbon black"—it achieves the controllable preparation of titanium carbide nanoparticles with an average particle size of 40-60 nm and a sphericity >0.90 in this reaction system. This overcomes the long-standing limitation of this reaction route in simultaneously achieving a regular spherical morphology at the nanoscale.

[0037] (ii) Significant synergistic effects among multiple strategies The various technical features of this invention are not simply superimposed, but rather produce a significant synergistic effect: The matching use of spherical titanium powder templates and low-structure carbon black: Both raw materials have near-spherical microstructure characteristics, forming a morphology transfer chain of "spherical template → spherical coating → spherical product" in the entire process of ball milling-reaction-cooling, which is a double guarantee for ensuring sphericity.

[0038] The complementary nature of physical isolation by molten salt and chemical pinning by excess carbon black: molten salt addresses long-range migration and contact sintering between particles, while excess carbon black addresses short-range diffusion and Ostwald ripening on the surface of individual particles. Both inhibit grain growth at the "inter-particle" and "particle surface" scales, respectively, forming a protective closed loop.

[0039] The timing of multi-stage heating and segmented controlled-rate cooling is coordinated: during the heating stage, slow melting of molten salt ensures the uniform formation of the "micro-reaction pool," while rapid heating to the reaction temperature shortens the residence time in the intermediate temperature zone; during the cooling stage, rapid cooling in the high-temperature zone freezes the particle size, while slow cooling in the intermediate temperature zone prevents thermal stress cracking. The two stages work in tandem on the timeline to jointly maintain the nanoscale particle size.

[0040] (iii) The reaction temperature was significantly reduced. By introducing lattice defects and amorphization through high-energy ball milling activation, the onset temperature of the Ti+C carbide reaction was reduced from the conventional 1100-1200℃ to 900-1000℃, a decrease of approximately 200℃. This reduction in reaction temperature directly weakens the thermodynamic driving force for grain growth, creating favorable conditions for grain size control.

[0041] (iv) The product has high purity and excellent quality. Through systematic atmosphere protection and pollution control (gas purifier to reduce O2 and H2O in Ar to <0.1ppm, pipeline pretreatment, and full-process operation in glove box), in-situ deoxygenation of excess carbon, and deep water washing purification (conductivity <5μS / cm), the obtained TiC nanoparticles have an oxygen content of <0.5wt%, residual carbon of <3wt% under optimal conditions, and no impurity phases such as TiO2. XRD shows a pure-phase cubic structure of TiC.

[0042] (v) The process is simple and suitable for large-scale production. This invention adopts the simplest route of direct reaction between metallic titanium powder and carbon black, without involving complex organic synthesis or expensive equipment. The process is short, the operating window is wide (temperature adjustable from 900 to 1000℃, salt ratio adjustable from 5:1 to 20:1), and it is easy to scale up and industrialize.

[0043] (vi) Good adaptability to raw materials Although spherical titanium powder is preferred, by extending the ball milling time (e.g., 24-36 hours), micron-sized irregular titanium powder can also be sufficiently refined and nearly spherical TiC nanoparticles can be prepared (verified in Example 2), reducing the raw material threshold and cost.

[0044] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0045] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 This is a process flow diagram of the method for preparing spherical titanium carbide nanoparticles according to the present invention; Figure 2 This is a schematic diagram of the multi-segment temperature rise and fall control curve of the present invention; Figure 3 This is a schematic diagram comparing the segmented speed-controlled cooling curve and the furnace-fed cooling curve of the present invention; Figure 4 This is a schematic diagram showing the separation state of the components before ball milling in this invention; Figure 5 This is a schematic diagram of the precursor / salt composite microregion formed after ball milling according to the present invention; Figure 6 This is a schematic diagram of the micro-reaction pool formed during the molten salt carbonization stage of the present invention; Figure 7This is a schematic diagram of a transmission electron microscope (TEM) image of the spherical titanium carbide nanoparticles obtained in Example 1 of the present invention; Figure 8 This is a schematic diagram of the X-ray diffraction (XRD) pattern of the spherical titanium carbide nanoparticles obtained in Example 1 of the present invention. Detailed Implementation

[0046] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0047] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.

[0048] All raw materials used in the embodiments are commercially available, and the equipment used is conventional equipment in the art. The sphericity described in this invention is characterized by roundness, i.e., sphericity = 4πA / P² (where A is the projected area of ​​the particle and P is the projected perimeter of the particle). The sphericity is calculated by randomly selecting at least 200 particles from transmission electron microscopy (TEM) images using image analysis and taking the arithmetic mean.

[0049] Example 1 S1. Raw material preparation Weigh out 150g of NaCl and KCl (molar ratio 1:1), place them in a vacuum drying oven, and dry them at 200℃ and a vacuum degree <-0.1MPa for 24 hours. After drying, grind them thoroughly in an argon glove box (O2 <0.1ppm, H2O <0.1ppm) using an agate mortar, seal and store for later use.

[0050] Weigh the following raw materials in an argon glove box: Spherical titanium powder (average particle size 30-40 nm, sphericity >0.85, purity >99.5%): 1.0 g. This invention can be achieved with titanium powder having an average particle size ≤50 nm; in this embodiment, 30-40 nm is preferred. Low-structure ultrafine carbon black (primary particle size 30-50 nm, specific surface area 50-80 m² / g, DBP value 120-150 mL / 100 g): 0.29 g (corresponding to Ti:C=1:1.15). The carbon black can have a primary particle size of 30-50 nm, a specific surface area ≥50 m² / g, and an oil absorption value (DBP) within the range of 100-200 mL / 100 g; the above specifications are preferred in this embodiment. The molar ratio of titanium powder to carbon black, Ti:C, can be 1:1.1-1.3; 1:1.15 is preferred in this embodiment. When Ti:C is 1:1.1, the residual carbon is lower; when Ti:C is 1:1.3, the particle size is smaller but the residual carbon is increased (Example 4). Molten salt: 13g (the total mass ratio of salt to reactant Ti+C is approximately 10:1). The mass ratio of molten salt to the total mass of titanium powder and carbon black can be in the range of 5:1-20:1, and in this embodiment, approximately 10:1 is preferred. Increasing the proportion of molten salt within this range increases the number of liquid "micro-reaction pools" and reduces the particle size. When the ratio is reduced to 5:1, the particle size increases (Example 3).

[0051] S2, High-energy ball milling activation Transfer the above powder to a 100 mL titanium carbide grinding jar, add titanium carbide grinding balls (5-10 mm in diameter), with a ball-to-powder ratio of 15:1. Add 15-20 mL of anhydrous cyclohexane (pre-dried with molecular sieves) as the wet grinding medium (anhydrous ethanol can also be used). Seal the grinding jar in a glove box. The grinding jar and grinding media are made of titanium carbide, or zirconium oxide.

[0052] Ball milling procedure: Premixing stage 200 rpm, 1 hour; high-energy grinding stage 400 rpm, 15 hours, ball-to-material ratio 15:1. Stop the mill for 15 minutes every 3 hours of ball milling to prevent overheating. A ball milling speed of 400-600 rpm, a milling time of 12-20 hours, and a ball-to-material ratio of 10:1-20:1 are all acceptable; in this embodiment, 400 rpm, 15 hours, and 15:1 are preferred. After ball milling, return the milling jar to the glove box, open it, and remove the slurry. Remove cyclohexane at 60°C under vacuum to obtain a dry precursor powder. Lightly grind the powder in an agate mortar until no large particles are visible to the naked eye.

[0053] Figures 4 to 6 This illustrates the principle of high-energy ball milling activation and isolation from the molten salt medium. For example... Figure 4 As shown, before ball milling, the titanium powder, carbon black, and molten salt components are separated from each other, and the titanium particles, carbon black particles, and salt grains are only in a physically mixed state; as Figure 5 As shown, after high-energy ball milling, nano-sized titanium particles and carbon black particles are uniformly embedded inside the salt grains, forming a "precursor / salt" composite micro-region, which lays the structural foundation for the subsequent formation of the molten salt "micro-reaction pool".

[0054] S3, carbonization reaction Inside the glove box, spread the precursor powder evenly in the corundum boat, with a thickness not exceeding 3 mm. Place the corundum boat into a sealed transfer container, remove it from the glove box, and connect it to the tube furnace inlet.

[0055] Close the furnace tube exhaust valve and turn on the vacuum pump to evacuate to ≤10. - Maintain the pressure at 2 Pa for 10 minutes. Close the vacuum valve and purge with high-purity argon gas (treated by a gas purifier, O2 < 0.1 ppm) to approximately 0.11 MPa. Repeat the vacuum-purging cycle three times. After the last purging, maintain the Ar flow rate at 100 mL / min (within the range of 50-200 mL / min is acceptable). Connect a trace oxygen analyzer to the exhaust outlet and begin heating after confirming the oxygen content is < 1 ppm.

[0056] The multi-stage heating program was run, and the temperature range, heating rate, holding time, and atmosphere for each stage are shown in Table 1. The furnace temperature-time curve is shown in... Figure 2 As shown.

[0057] Table 1

[0058] like Figure 2 As shown, in stage I, the temperature is rapidly increased from room temperature to 200°C to remove physically adsorbed water; in stage II, the temperature is increased to 400°C at a medium rate and held for 60 minutes, during which a mixture of Ar and 5% H2 gas is introduced for pre-reduction and deoxygenation; in stage III, the temperature is increased slowly to 700°C at a rate of 2°C / min and held for 30 minutes, during which the molten salt melts and the gas is released, forming a liquid "micro-reaction pool" coating the reactant particles, as shown in the figure. Figure 6 As shown, individual TiC nanoparticles are generated in each microreactor, and liquid salt isolates the particles from each other. Stage IV rapidly heats up to 1000℃, shortening the residence time in the intermediate temperature zone. Stage V is held at 1000℃ for 180 min for carbonization. The heating rates for each stage can be within the following ranges: Stage I 8-12℃ / min, Stage II 4-6℃ / min, Stage III 1-3℃ / min, Stage IV 4-6℃ / min, and Stage V holding for 120-240 min. The carbonization reaction temperature can be within the range of 900-1000℃, and in this embodiment, the parameters listed in Table 1 and 1000℃ are preferred.

[0059] After Phase II is completed, the atmosphere is switched from Ar + 5% H2 back to pure Ar, and the pipeline is purged with pure Ar for 10 minutes to remove residual H2 before further heating.

[0060] S4, Segmented Speed ​​Controlled Cooling After the carbonization reaction was completed, the furnace temperature was reduced to room temperature according to the segmented rate-controlled cooling procedure shown in Table 2. The cooling curve is as follows: Figure 3 As shown.

[0061] Table 2

[0062] like Figure 3 As shown, the solid line represents the segmented controlled-rate cooling curve of this embodiment: rapid cooling at 12℃ / min from 1000℃ to 800℃ (programmed temperature control combined with auxiliary airflow cooling), taking approximately 17 minutes to traverse the high-temperature zone and freeze the grain size; medium-speed cooling at 6℃ / min from 800℃ to 500℃ (programmed temperature control), taking approximately 50 minutes to allow the molten salt matrix to solidify and shrink uniformly, preventing TiC particles from breaking due to thermal stress; natural cooling from 500℃ to room temperature (heating power off, maintaining Ar flow). The dashed line in the figure represents the furnace cooling curve (approximately 3℃ / min), for comparison (see Example 6). The cooling rate for each segment can be within the following ranges: 10-15℃ / min from 1000℃ to 800℃, and 5-8℃ / min from 800℃ to 500℃. In this embodiment, 12℃ / min and 6℃ / min are preferred.

[0063] S5, Post-processing After the furnace temperature drops to <50℃, close the vent valve, quickly remove the corundum boat and place it in a sealed transfer container, then transfer it to a glove box. Transfer the lumpy product to a beaker, add 200mL of deionized water (resistivity >18MΩ·cm), and place it in an 80℃ water bath with magnetic stirring (200-300rpm) for 4 hours (solid-liquid ratio approximately 1:50-1:100, temperature 70-90℃, soaking time 2-8 hours are acceptable). During this period, replace the deionized water once, and sonicate for 10-15 minutes every hour.

[0064] Vacuum filtration was performed using a PTFE microporous membrane with a pore size of 0.22 μm (vacuum degree -0.05 to -0.07 MPa). The filter cake was redispersed in 150 mL of fresh 80 °C deionized water, stirred for 30 minutes, and filtered again. The washing cycle was repeated at least 6 times, and the conductivity of the filtrate was measured each time until the conductivity was <5 μS / cm. At the same time, 0.1 mol / L AgNO3 solution was added dropwise to check for the absence of white precipitate.

[0065] Spread the washed filter cake evenly in a PTFE tray, with a thickness not exceeding 5 mm, and place it in a vacuum drying oven at 80°C and a vacuum degree <-0.1 MPa for 20 hours (drying temperature can be within the range of 60-80°C and drying time is within the range of 12-24 hours; in this embodiment, 80°C and 20 hours are preferred). After drying, gently grind the filter cake in a glove box with an agate mortar for 5 minutes, and then transfer it to a glass sample bottle for sealed storage.

[0066] Product characterization XRD ( Figure 8 ):like Figure 8As shown, the product exhibits diffraction peaks near 2θ of 36°, 42°, 60°, 72° and 76°, corresponding to the (111), (200), (220), (311) and (222) crystal planes of cubic TiC, respectively, consistent with the standard card JCPDS 32-1383. There are no characteristic peaks of TiO2 or residual Ti, indicating that the product is pure-phase cubic TiC. TEM Figure 7 ):like Figure 7 As shown (scale bar 50nm), the particles are nearly spherical, well dispersed, and without obvious hard agglomeration. Among 200 particles, the average particle size is 48±8nm, and the sphericity is >0.92. TGA (air, room temperature to 800°C): residual carbon content 2.3 wt%; LECO Oxygen and Nitrogen Analyzer: Oxygen content 0.35 wt%; ICP-OES: Fe<50ppm, Cr, Ni<20ppm.

[0067] Example 2 The raw material titanium powder used was micron-sized irregular hydrogenated dehydrogenated (HDH) titanium powder (average particle size approximately 10 μm, flake-like), and the carbon black, molten salt, and proportions were the same as in Example 1. To adapt to the change in raw materials, the process was adjusted as follows: the high-energy ball milling time was extended to 24 hours, the ball-to-powder ratio was increased to 20:1, and the rotation speed was 500 rpm; the amount of anhydrous cyclohexane used as a process control agent was increased to 25 mL; other steps were the same as in Example 1. The obtained TiC nanoparticles had an average particle size of 52 ± 10 nm, sphericity > 0.88, oxygen content of 0.42 wt%, and XRD showed pure phase TiC. This indicates that through sufficient ball milling refinement, near-spherical nano-TiC particles can also be prepared from micron-sized irregular titanium powder.

[0068] Example 3 The mass ratio of molten salt to reactant (Ti+C) was reduced to 5:1, with other conditions remaining the same as in Example 1. The resulting TiC nanoparticles had an average particle size of 65±12 nm, sphericity >0.85, and oxygen content of 0.40 wt%. This indicates that reducing the amount of molten salt resulted in a decrease in the number and size of liquid "micro-reaction cells," a decline in physical isolation, and a slight increase in particle size.

[0069] Example 4 The Ti:C molar ratio was increased to 1:1.30 (i.e., 30% carbon excess), with all other conditions remaining the same as in Example 1. The resulting TiC nanoparticles had an average particle size of 45±7 nm and a sphericity >0.90, but the residual carbon content increased to 4.2 wt%. This indicates that increasing the carbon excess ratio helps to further suppress particle growth, but it introduces more residual carbon contamination. Ti:C = 1:1.15 is the preferred value that balances particle size control and product purity.

[0070] Example 5 Molten salt was not used, and all other conditions were exactly the same as in Example 1 (the ratio of titanium powder and carbon black, as well as the ball milling, heating, cooling, and post-treatment procedures were all the same).

[0071] Results: The product after carbonization was a bulk sintered body. TEM observation after grinding showed an average particle size >200 nm, with an irregular polyhedral morphology and numerous fused particles. This indicates that without molten salt physical isolation, the strong exothermic reaction of Ti+C and interparticle sintering could not be suppressed, resulting in failure to control particle size. This comparative experiment verifies the crucial role of molten salt medium isolation in achieving the 50 nm particle size target.

[0072] Example 6 Instead of using the multi-stage heating program of this invention (which is replaced by direct heating to 1000°C at 10°C / min) and the segmented rate-controlled cooling program (which is replaced by furnace cooling at approximately 3-5°C / min, see cooling curve), this invention is no longer used. Figure 3 (dashed line), the other conditions (including molten salt, excess carbon, etc.) are the same as in Example 1.

[0073] Results: TEM observation showed an average particle size of 85±15 nm with a wide particle size distribution (40-150 nm), and some particles showed obvious grain fusion and abnormal growth. XRD showed narrow diffraction peaks, indicating a large average grain size. This indicates that even with excess molten salt and carbon, an unreasonable heating and cooling regime can still lead to significant grain growth, verifying the important contribution of precise thermal field management to particle size control.

[0074] Example 7 High-structure black (EC-300J, DBP value >300mL / 100g) was used instead of the low-structure carbon black in Example 1, the Ti:C molar ratio was kept at 1:1.15, and the other conditions were the same as in Example 1.

[0075] Results: TEM observation revealed a large number of grape-like aggregates formed by carbon skeletons in the product. Although individual particles were nanometer-sized (~50 nm), the aggregate size reached 200-500 nm, making them impossible to disperse and dissociate by conventional ultrasonication. The sphericity score was <0.80. This indicates that the structure degree (morphological characteristics) of carbon black directly affects the dispersion state and sphericity of the product, verifying the necessity of selecting low-structure carbon black.

[0076] This invention addresses two long-standing technical challenges in the direct reaction of titanium powder and carbon black (Ti+C→TiC) route: uncontrollable product particle size (easily growing to submicron size) and irregular morphology. It proposes a multi-strategy synergistic systemic solution. Through a three-pronged strategy of "spherical titanium powder template inheritance + physical isolation in a molten salt microreactor + chemical pinning with excess carbon black" to synergistically control morphology and particle size, coupled with a refined multi-stage heating and segmented rate-controlled cooling thermal field management system, the controllable preparation of titanium carbide nanoparticles with an average particle size of 40-60 nm and a sphericity greater than 0.90 has been successfully achieved in the Ti+C direct reaction system.

[0077] Comparative experiments (Examples 5-7) verified the necessity and synergistic effect of the core technical features of this invention: without molten salt, the particle size becomes uncontrolled (>200nm); without precise thermal field management, the particle size increases significantly (85nm and wide distribution); and using high-structure carbon black deteriorates sphericity and dispersibility. The method of this invention uses inexpensive and readily available raw materials, has a simple process, good repeatability, and a wide operating window, showing promising prospects for industrial application and providing a practical technical solution for the large-scale production of spherical titanium carbide nanoparticles.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black, characterized in that, Includes the following steps: S1. Raw material preparation: Weigh spherical titanium powder, carbon black, and NaCl-KCl molten salt in an inert atmosphere glove box; the average particle size of the spherical titanium powder is ≤50nm and the sphericity is >0.85; the carbon black is low-structure ultrafine carbon black with a primary particle size of 30-50nm; the molar ratio of the spherical titanium powder to the carbon black is Ti:C = 1:1.1-1.3; the mass ratio of the NaCl-KCl molten salt to the total mass of the spherical titanium powder and carbon black is 5:1-20:1; S2, High-energy ball milling activation: The raw material obtained in S1 is subjected to high-energy ball milling under an inert atmosphere to obtain precursor powder; S3, Carbonization reaction: Place the precursor powder obtained in S2 in an inert atmosphere, raise the furnace temperature to 900-1000℃ according to a multi-stage heating program to carry out the carbonization reaction, and hold for 120-240 minutes. S4. Segmented controlled-rate cooling: After the carbonization reaction is completed, first cool from the reaction temperature to 800℃ at a cooling rate of 10-15℃ / min, then cool from 800℃ to 500℃ at a cooling rate of 5-8℃ / min, and then cool naturally to room temperature. S5. Post-treatment: The product obtained in S4 is washed with water to remove salt and then vacuum dried to obtain spherical titanium carbide nanoparticles.

2. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S1, the average particle size of the spherical titanium powder is 30-40 nm, and the purity is >99.5%; the NaCl-KCl molten salt is obtained by mixing NaCl and KCl in a molar ratio of 1:1 and then pre-treating by vacuum drying, the vacuum drying temperature is 150-250℃, and the time is 12-48 hours; the mass ratio of the NaCl-KCl molten salt to the total mass of the spherical titanium powder and carbon black is 10:

1.

3. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S1, the carbon black has a specific surface area ≥ 50 m² / g and an oil absorption value (DBP) of 100-200 mL / 100 g; the molar ratio of the spherical titanium powder to the carbon black is Ti:C = 1:1.

15.

4. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S2, the high-energy ball mill rotates at 400-600 rpm, mills for 12-20 hours, and has a ball-to-material ratio of 10:1-20:

1. The high-energy ball mill uses a wet milling method, with anhydrous cyclohexane or anhydrous ethanol as the wet milling medium. After milling, the wet milling medium is removed by vacuum drying. The milling jar and the milling medium are made of titanium carbide cemented carbide or zirconium oxide.

5. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S3, the multi-stage heating program includes: Stage I, heating from room temperature to 200℃ at a rate of 8-12℃ / min; Stage II, heating from 200℃ to 400℃ at a rate of 4-6℃ / min, and holding at 400℃ for 30-90 minutes; Stage III, heating from 400℃ to 700℃ at a rate of 1-3℃ / min, and holding at 700℃ for 20-40 minutes; Stage IV, heating from 700℃ to the reaction temperature at a rate of 4-6℃ / min; and Stage V, holding at the reaction temperature for 120-240 minutes.

6. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 5, characterized in that: In S3, a mixture of Ar and 5% H2 gas is introduced into stage II; after the heat preservation is completed, the atmosphere is switched back to pure Ar, and the gas is purged with pure Ar for 10 minutes before subsequent heating.

7. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In step S3, the precursor powder is spread evenly in a corundum container, with a powder thickness not exceeding 5 mm; the furnace tube is evacuated and purged with inert gas at least three times, until the pressure inside the furnace tube is ≤10. - ²Pa; After the last inflation, maintain the inert gas flow rate at 50-200 mL / min.

8. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S4, the cooling rate from the reaction temperature to 800℃ is 12℃ / min, using programmed temperature control combined with auxiliary airflow cooling; the cooling rate from 800℃ to 500℃ is 6℃ / min, using programmed temperature control; and inert gas is maintained during the natural cooling from 500℃ to room temperature.

9. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 1, characterized in that: In S5, the water washing and desalination is performed as follows: the product is placed in deionized water with a solid-liquid ratio of 1:50-1:100, heated to 70-90℃ and stirred, soaked for 2-8 hours, and then separated into solid and liquid by vacuum filtration using a filter membrane with a pore size of 0.22μm. The product is then repeatedly washed until the conductivity of the filtrate is <5μS / cm. The vacuum drying is performed at 60-80℃ and a vacuum degree <-0.1MPa for 12-24 hours. After vacuum drying, the product is ground in an inert atmosphere using an agate mortar for 5-10 minutes.

10. The method for preparing spherical titanium carbide nanoparticles based on the direct reaction of metallic titanium powder and carbon black according to claim 2, characterized in that: The obtained spherical titanium carbide nanoparticles have an average particle size of 40-60 nm, a sphericity greater than 0.90, an oxygen content of less than 0.5 wt%, and XRD shows that they are pure-phase cubic TiC structures.

Citation Information

Patent Citations

  • Method for preparing titanium carbide powder by high-frequency induction-carbothermic reduction

    CN101734659A

  • Preparation method for titanium carbide nanoparticles

    CN102674350A

  • Method for synthesizing titanium carbide powder by high frequency induction heat explosion

    CN104230343A

  • Preparation method of titanium carbide fiber

    CN117051507A

  • Method of preparing titanium carbide material using fused salt method

    CN1299982C